Achieving superior ductility for laser directed energy deposition 300 M steel through isothermal bainitic transformation. (December 2020) - Liu, Fenggang; Zhang, Wenjun; Lin, Xin; Huang, Chunping; Wang, Zhitai; Liu, Fencheng; Huang, Weidong; Wang, Pengfei; Li, Xun
Highlights: The microstructure of as-deposited LDED 300 M steel is different from that of forgings. After isothermal heat treatment, the microstructure of LDED 300 M steel is refined. The ductility of LDED 300 M steel with isothermal heat treatment exceeds the forged standard. The work hardening behavior of LDED 300 M steel is analyzed by true stress-strain curves. Abstract: The microstructure evolution and tensile properties of laser directed energy deposition (LDED) 300 M steel with isothermal heat treatment at 320 ℃ for different holding time were investigated in this paper. The results showed that the microstructure of the as-deposited LDED 300 M steel consisted of martensite and bainite. After heat treatment, the microstructure of the LDED 300 M steel is still the mixture of martensite, bainite and retained austenite, while the size of the lower bainite significantly decreased. As the increasing holding time, the content of martensite gradually decreased, while the content of bainite and austenite gradually increased. When the holding time of LDED 300 M steel increased from 20 min to 40 min, the number and size of austenite increased slightly. However, when the holding time was 60 min, the number and size significantly increased. As holding time continuously increase, it contributes little to the number and size of austenite. With regard to the hardness of the LDED 300 M steel, it was 464 HV when the holding time was 20 min. With the increment of holding time, the hardness gradually decreased until 428 HV when the holding time was 80 min. While holding time had less effect on the tensile strength and yield strength. To be specific, the tensile strength decreased from 1348 MPa to 1332 MPa, and yield strength decreased from 853 MPa to 759 MPa. The elongation gradually increased, and it increases to 33 % when the holding time was 80 min, which was higher than that of the forged 300 M steel standard (15 %). Effect of various factors, like microstructure, dislocation density and ε-carbides precipitated in the bainite on the ductility of the LDED 300 M steel with isothermal heat treatment was also studied.